Instant IELTS - Hart, Guy Brook (Tp. Hồ Chí Minh,Tổng hợp Tp. Hồ Chí Minh, 2004)
This photocopiable resource is packed with a range of ready-to-use IELTS exam practice activities. The lively discussions and role plays that accompany them turn each IELTS task-type into a stimulating lesson. The book is organised by paper type, giving teachers a flexible resource that they can tailor to their students' specific needs.